2009
DOI: 10.1088/0953-8984/22/2/025701
|View full text |Cite
|
Sign up to set email alerts
|

Correlated magnetic impurities in a superconductor: electron density profiles and robustness of superconductivity

Abstract: The insertion of magnetic impurities in a conventional superconductor leads to various effects. In this work we show that the electron density is affected by the spins (considered as classical) both locally and globally. The charge accumulation is solved self-consistently. This affects the transport properties along magnetic domain walls. Also, we show that superconductivity is more robust if the spin locations are not random but correlated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Magnetism and superconductivity typically compete and, therefore, most heterostructures considered tend to separate the ferromagnetic and superconducting regions (often separated by an insulator to prevent proximity effects). The presence of randomly located magnetic impurities in a conventional superconductor destroys the superconducting order for small impurity concentrations 18 but we have shown 19,20 that, if the magnetic moments are correlated, superconductivity is much more robust and prevails for much higher concentrations. Therefore, if the magnetic moments are somewhat diluted we expect that superconducting order should remain.…”
Section: Introductionmentioning
confidence: 80%
“…Magnetism and superconductivity typically compete and, therefore, most heterostructures considered tend to separate the ferromagnetic and superconducting regions (often separated by an insulator to prevent proximity effects). The presence of randomly located magnetic impurities in a conventional superconductor destroys the superconducting order for small impurity concentrations 18 but we have shown 19,20 that, if the magnetic moments are correlated, superconductivity is much more robust and prevails for much higher concentrations. Therefore, if the magnetic moments are somewhat diluted we expect that superconducting order should remain.…”
Section: Introductionmentioning
confidence: 80%
“…Finally we have shown that the Hall conductance tracks the quantum phase transition induced by magnetic impurities in conventional superconductors. This provides transport measurement as a possible tool to detect the transition, related to earlier predictions that transport properties are affected by the presence of magnetic impurities in a superconductor [59]. We note that one of the interests of the AHE is that it can be easily measured.…”
Section: Discussionmentioning
confidence: 62%
“…The gap function renormalization in the system of two impurities was recently revisited 79 . Similarly to a pair of magnetic impurities also ordered magnetic chains undergo a series of first order QPTs as the exchange interaction of magnetic moments is increased 3,18,25 . These phase transitions are induced by numerous level crossings between the ingap states and can be observed in changes of total magnetization of the electron spin density, local spin density, local density of states, various quantum information measures and the local order parameter.…”
Section: Quantum Phase Transitionsmentioning
confidence: 99%
“…If the magnetic impurities have arbitrary orientations and locations on the superconductor the pair breaking effect leads to gapless superconductivity and eventually destruction of superconductivity [24] for small concentration of impurities of the order of a few percent. A higher robustness of superconductivity to the increasing number of magnetic impurities has been found if they are correlated, particularly if their locations are not random but organized in some patterns [25]. These regular distributions allow quite high concentrations of impurities without destruction of superconductivity.…”
Section: Introductionmentioning
confidence: 99%